Acquired cutaneous Langerhans cell histiocytosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
A 5-month-old child was first observed with a history of micropustules of the hips not responsive to topical therapy. The child had an atopic family history (seasonal rhinitis and oral allergic syndrome in the mother) and assumed a "hypoallergenic" milk after an episode of gastroenteritis during the first days of life. The dermatological examination revealed a modest follicular keratosis. The child came again to visit after 1 month because, despite a normal growth, his mother noticed punctiform crusts on the scalp and in the retroauricular region; moreover, from 10 days the mother noticed punctate lesions of the pubis (Fig. 1) and scalp. This time the physical examination showed a ten purpuric papules in the hypogastric region. The blood tests and ultrasound examinations were normal, but histology of a papule showed in the edematous papillary dermis an infiltration of eosinophils and large CD1a+ and S-100+ histiocytes (Fig. 2), leading to diagnose acquired cutaneous Langerhans cell histiocytosis and to program a follow-up program with the oncohematologist.